The making of Selim succession, legitimacy, and memory in the early Modern Ottoman World - Çıpa, H. Erdem 1971- (Indiana University Press, 2017)
The father of the legendary Ottoman sultan Suleyman the Magnificent, Selim I ("The Grim") set the stage for centuries of Ottoman supremacy by doubling the size of the empire. Conquering Eastern Anatolia, Syria, and Egypt, Selim promoted a politicized Sunni Ottoman identity against the Shiite Safavids of Iran, thus shaping the early modern Middle East. Analyzing a wide array of sources in Ottoman-Turkish, Persian, and Arabic, H. Erdem Cipa offers a fascinating revisionist reading of Selim's rise to power and the subsequent reworking and mythologizing of his persona in 16th- and 17th-century Ottoman historiography. In death, Selim continued to serve the empire, becoming represented in ways that reinforced an idealized image of Muslim sovereignty in the early modern Eurasian world